ANALISIS NILAI KEMASLAHATAN DALAM PEMBERIAN HAK ASUH ANAK YANG BELUM MUMAYYIZ KEPADA AYAH PASCA PERCERAIAN (STUDI PUTUSAN NOMOR 1365/PDT.G/2021/PA.PLG) - Riana, Devi; Barkah, Qodariah; Wijaya, Sandy (Lembaga Marwah Rakyat, 2024)
Based on Article 105 of the Compilation of Islamic Law, children who are not yet mumayyiz have parental rights to the mother, and those who have mumayyiz are free to choose to follow the father or mother. However, in reality, the decision in the Class 1A Palembang Religious Court Number 1365/Pdt.G/2021/PA.Plg, children who are not yet mumayyiz, their parental rights fall to the father. This study aims to analyze the basis for the judge's consideration in giving custody of children who are not yet mumayyiz to the father and analyzing the value of its benefits. This research was conducted using the normative juridical method. The data sources used are primary data sources in the form of Palembang Religious Court decisions and secondary data sources in the form of previous literature, books, articles and related journals. Furthermore, the data was analyzed descriptively qualitatively. The results showed that the judge decided with a contrario decision by considering the sociological aspect, seeing where the child's condition was better and the judge made ijtihad in deciding this case. The analysis of the value of the benefit, with the theory of mashlaḥah mursalah and included in the mashlaḥah dharūrīyat and included the category of fiqh rules that harm should be eliminated. The judge also considered that fulfilling the five main objectives of Islamic law for the benefit of children includes three important things, namely in order to preserve the soul (Ḥifzh Al-Nafs), preserve the mind (Ḥifzh Al-'Aql), and preserve religion (Ḥifzh Al-Dīn)